The Effect of Immersion Time on The Ability of Tannins to Inhibit The Corrosion Rate of Mild Steel In 1M H2SO4 Solution - Pramudita, Marta; Sukirno, Sukirno; Nasikin, Mohammad (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2020)
Tannin is a polyphenol compound that is widely found in various types of plants. Polyphenol compounds can inhibit the corrosion rate of mild steel. This study aims to determine the effect of immersion time on tannins' ability to inhibit the corrosion rate of mild steel in 1M sulfuric acid. The method used is weight loss with immersion time variations of 2,4 and 6 hours, temperature variations of 313K, 333K, and 353K. The concentration variation used was 0; 250; 500; 750; 1000; 1250 ppm. From the research results, it was found that the immersion time affected tannins' ability to inhibit corrosion in mild steel. The highest efficiency was 71.07% at a concentration of 1250 ppm and 313K. The longer the immersion time, the lower the tannin ability to inhibit corrosion in mild steel.